Clinical Characteristics and Outcomes of Patients Hospitalized with COVID-19 at Case Hospital, Uganda - Apiyo, Mirriam; Olum, Ronald; Kabuye, Amina; Khainza, Betty; Amate, Anne M.; Byabashaija, Vittal; Nomujuni, Derrick; Sebbaale, Kato; Senfuka, Peter; Kazibwe, Simon; Sharma, Gurav; Davidson, Lindsay; et al. (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Data on clinical outcomes of patients hospitalized with coronavirus disease 2019 (COVID-19) in private health facilities in Uganda is scarce. We conducted a retrospective cohort study of patients hospitalized with COVID-19 at Case Hospital, Kampala, Uganda, between June 2020 and September 2021. Data of 160 participants (median age 45 years (interquartile range [IQR]: 37–57) and 63.5% male) was analyzed. Seventy-seven (48.1%) participants had non-severe, 18 (11.3%) severe, and 83 (51.9%) critical COVID-19 illness. In 62 participants with chest computed tomography findings, 54 (87%) had bilateral disease, with 22 (35%) having ground-glass opacities. The median duration of hospitalization was 5 days (IQR: 3–9 days). Overall, 18 (11.3%) participants died. Survival at 14 and 28 days was 89% and 72%, respectively. Factors strongly associated with all-cause mortality were as follows: age >50 years (odds ratio [OR]: 8.6, 95% confidence interval [CI]: 1.1–69.2, and p=0.042), having at least 1 comorbidity (OR: 3.2, 95% CI: 1.1–8.9, and p=0.029), hypertension (OR: 3.2, 95% CI: 1.2–8.6, and p=0.024), diabetes mellitus (OR: 2.9, 95% CI: 1.0–8.5, andp=0.056), and oxygen saturation <92% (OR: 5.1, 95% CI: 1.8–14.4, and p=0.002). In this private health facility, mortality was about 1 in 10 patients, and more people presented with critical illness in the second wave of the pandemic, and most deaths occurred after 2 weeks of hospitalization.